2021
DOI: 10.1177/00131245211027363
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Exploration of the Relationship between Veteran Family Membership, School Climate, and Adverse Outcomes among School-Aged Youth

Abstract: Little is known about the functioning of children in veteran-connected families, who may experience a unique constellation of stressors including exposure to parental mental health symptoms and unemployment. Further, research has not previously considered the role of school climate in counteracting these stressors for veteran-connected students. This preliminary study examines the relationship between veteran parent’s mental health and employment with adverse outcomes for their school-age children, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(79 reference statements)
1
1
0
Order By: Relevance
“…Specifically, the higher the school mental health service, the stronger the positive association between the parents’ mental health literacy, parent-child intimacy, and adolescents’ mental health literacy. In line with Sullivan et al 55 they found the moderating effect of school climate on the relationship between parents’ mental health and children’s adverse outcomes. Our results also found a positive role for school.…”
Section: Discussionsupporting
confidence: 71%
“…Specifically, the higher the school mental health service, the stronger the positive association between the parents’ mental health literacy, parent-child intimacy, and adolescents’ mental health literacy. In line with Sullivan et al 55 they found the moderating effect of school climate on the relationship between parents’ mental health and children’s adverse outcomes. Our results also found a positive role for school.…”
Section: Discussionsupporting
confidence: 71%
“…In order to ensure that the development of education plans is scientific and reasonable, teachers need to strengthen communication with relevant enterprises, jointly develop education plans, and improve the contemporary characteristics of education plans, thereby improving the employment management of college students. Secondly, in order to ensure that college students have strong employability to cope with future employment upon graduation, teachers need to strictly follow the basic principle of comprehensiveness when formulating education plans and take the following as the main entry point for the formulation of education plans: promoting the comprehensive development of college students' morality, intelligence, physical fitness, aesthetics, and labor [16] . Thirdly, when formulating education plans, teachers must implement the educational philosophy of applying knowledge and combining learning with application, vigorously cultivate college students' knowledge application and practical abilities, as well as organize targeted professional skill training for students.…”
Section: Strengthen the Optimization Of Education Plansmentioning
confidence: 99%